IMPLEMENTATION OF THE QUIZIZZ APPLICATION AS A MEDIA IN ASSESSMENT OF ONLINE LEARNING TO GROW STUDENT LEARNING MOTIVATION IN ELEMENTARY SCHOOLS - Kharisma Romadhon; Lusi Oktavia; Irfan Irfan; Putri Jannati; Anelda Ultavia (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2023)
Learning motivation is the key to success in teaching and learning assessment activities in elementary schools. However, learning assessment instruments so far tend to be monotonous and boring for students. The purpose of this research is to describe how the application of the Quizizz application which is a medium for conducting assessments in online learning, and to describe the increase in students' learning motivation through this Quizizz application. The research method used is qualitative with a descriptive approach, the results of interviews and observations are a data collection technique in this study. The research was carried out at Al-Azhar Islamic Elementary School, Cairo, Pagar Alam City, South Sumatra. The results of research in the field prove that the application of the Quizizz application, which is a medium in the assessment of the teaching and learning process, can foster interest and motivation to learn. This can be seen from the activeness and enthusiasm of student learning, competing to get high scores, and so on. Through the Quizizz application, students can learn while playing.